NORMATIVE-LEGAL BASES OF THE ORGANIZATION OF INDEPENDENT EDUCATION (Conference Zone, 2022)
Today, the main tasks of modern education are the development of students' skills of independent critical thinking, information retrieval and retrieval, intellectual work culture, independent learning.